Evaluation of the SCKnowIQ Tool and Reproductive CHOICES Intervention Among Young Adults With Sickle Cell Disease or Sickle Cell Trait. (August 2014) - Gallo, Agatha M.; Wilkie, Diana J.; Wang, Edward; Labotka, Richard J.; Molokie, Robert E.; Stahl, Christiane; Hershberger, Patricia E.; Zhao, Zhongsheng; Suarez, Marie L.; Johnson, Bonnye; Pullum, Cherese; Angulo, Rigoberto; et al.
The study purpose was to evaluate a computer-based questionnaire (SCKnowIQ) and CHOICES educational intervention using cognitive interviewing with childbearing-aged people with sickle cell disease (SCD) or trait (SCT). Ten control group participants completed the SCKnowIQ twice. Ten intervention group participants completed the SCKnowIQ before and after the CHOICES intervention. Most participants found the questionnaire items appropriate and responded to items as the investigators intended. Participants' responses indicated that the information on SCD and SCT and reproductive options was understandable, balanced, important, and new to some. Internal consistency and test–retest reliability were adequate (.47 to .87) for 4 of the 6 scales, with significant within-group changes in knowledge scores for the intervention group but not for the control group. Findings show evidence for potential efficacy of the intervention, but proof of efficacy requires a larger randomized study.